Complete IELTS : - Harrison, Mark (Cambridge Univeristy, 2012)
Complete IELTS combines the very best in contemporary classroom practice with stimulating topics aimed at young adults wanting to study at university. This course covers all parts of the IELTS exam in detail, providing information, advice and practice to ensure that students are fully prepared for every aspect of the exam. Informed by the Cambridge English Corpus, Complete IELTS includes examples and exercises which tackle key IELTS problem areas, making it the most authoritative IELTS exam preparation course available. The Workbook with Answers with Audio CD contains extra practice corresponding to the units of the Student's Book.